From Historical Context to Contemporary Realities: Illicit Capital Outflows from Nepal - Ghimire, Dipesh K. (Molung Educational Frontier, 2024)
This paper explores illicit capital outflows, explaining its multifaceted implications in underdeveloped countries like Nepal. The paper also highlights the historical dynamics adjacent to illicit financial transfers, including their causes, mechanisms, and repercussions. The paper examines the various facets of illicit capital outflows, corruption, and bad governance mechanisms in Nepal. It explores how modern technology and global financial structures facilitate these outflows, contributing to a drain of resources from Nepal. Moreover, the study delves into historical contexts where significant capital outflows occurred due to political transitions and exploitation of national treasuries. The paper also discusses contemporary instances of illicit financial activities, including illegal transactions through Currency Smuggling, Hundi, and the involvement of banks and business entities in illegal capital flights from Nepal to abroad. It emphasizes the challenges faced by regulatory bodies in curbing these illicit practices and their adverse impacts on economic development, revenue collection, and the formal economy in Nepal.